Cover Image. (29th January 2020) - Mazzone, Luca; Moehrlen, Ueli; Ochsenbein‐Kölble, Nicole; Pontiggia, Luca; Biedermann, Thomas; Reichmann, Ernst; Meuli, Martin
Abstract : The cover image is based on the Original Article Bioengineering and in utero transplantation of fetal skin in the sheep model: A crucial step towards clinical application in human fetal spina bifida repair by Luca Mazzone, THOMAS BIEDERMANN, Ernst Reichmann et al., https://doi.org/10.1002/term.2963 .